The role of principled engagement in public health policymaking: the case of Zambia's prolonged efforts to develop a comprehensive tobacco control policy - Adam Silumbwe; Miguel San Sebastian; Joseph Mumba Zulu; Charles Michelo; Klara Johansson (Taylor & Francis Group, 2023)
Background The Framework Convention on Tobacco Control (FCTC) requires countries to develop and implement multi-sectoral tobacco control strategies, including policies and legislation. Zambia, potentially faced by a rising problem of tobacco smoking, signed the FCTC in 2008 but has been unable to enact a tobacco policy for over a decade. Objective This study explores the role of 'principled engagement', a key element of the theoretical framework for collaborative governance, in Zambia's delayed success to develop a comprehensive tobacco control policy. Methods This was a qualitative case study of key stakeholders in the collaborative process of trying to develop a tobacco policy in Zambia. Participan-ts were sampled from across various sectors, including government departments and civil society, comprising anti-tobacco activists and researchers. A total of 27 key informant interviews were undertaken. We supplemented the interview data with a document review of relevant policies and legislation. Data were analysed using thematic analysis. Results Several factors hindered efforts to attain principled engagement, including the adverse legal and socioeconomic environment in which the collaborative regime evolves; poor planning of meetings and frequent changes in tobacco focal point persons; lack of active and meaningful participation; and communication challenges among the key stakeholders. These collaborative dynamics, coupled with the opposition to tobacco control efforts from within some government departments, revealed the inadequacy of the current collaborative governance regime to facilitate enactment of a comprehensive tobacco control policy in Zambia. Conclusion Efforts to develop a comprehensive tobacco control policy in Zambia will require addressing challenges such as disagreements, communication, and leadership at engagement level across interested sectors. We further argue that principled engagement has a greater role to play in unlocking these efforts and should therefore be embraced by those entrusted to lead the process to develop tobacco policy in Zambia.